Growth differentiation factor 15 and its role in carcinogenesis: an update. (4th July 2019) - Modi, Anupama; Dwivedi, Shailender; Roy, Dipayan; Khokhar, Manoj; Purohit, Purvi; Vishnoi, Jeewanram; Pareek, Puneet; Sharma, Shailja; Sharma, Praveen; Misra, Sanjeev
Abstract: Growth differentiation factor-15 (GDF-15) is a novel cytokine secreted by a variety of cells like macrophages, adipocytes, normally expressed in high amounts by placenta. It is also highly expressed in multiple carcinomas like Colon, Breast, Pancreas, Liver, and Ovarian. Several reports on serum GDF-15 as a potential biomarker for diagnosis and prognosis of cancer are hampered by the lack of robust data, with large sample size and critical patient recruitment. However, experimental accounts on cancer tumors, cell lines, and animal models suggest GDF-15's role in cancer progression via endothelial mesenchymal transition, angiogenesis, metastasis, drug resistance and even stemness of various cancers. GDF-15 could be the point of amalgamation for the various hallmarks of cancer and can prove a useful therapeutic target in cancer. The current review was conceptualized with a thought of critically appraising the existing information of GDF-15 in carcinogenesis.